Pelatihan Penguatan Kemampuan Berbahasa Jepang Level Chukyu bagi Guru Bahasa Jepang di SMA dan SMK Kabupaten Buleleng Bali - Mardani, Desak Made Sri; Antartika, I Kadek; Suputra, Putu Hendra; Sadyana, I Wayan (Jurnal Pengabdian UNDIKMA, 2023)
The purpose of this community serviceÂ is to strengthen the Japanese language skills (Chukyu level) of Japanese High School/Vocational High School Teachers in Buleleng Regency so that their abilities increase and can pass the Teacher Professional Education/PPG. The method used in this activity is the Technical Assistance Model in the form of Training which is carried out by providing training and assistance to improve Japanese language skills. The partners in this activity were 20 (twenty) High School/Vocational High School Japanese language teachers in Buleleng Regency. The evaluation instrument for this activity is a test to determine the teacher's understanding of the material provided, as well as an assessment questionnaire by the teacher to evaluate the implementation of the activity. The results of tests and questionnaires were analyzed descriptively. The results of this activity show that through training and mentoring, the teachersâ€™ skills in reading discourse, knowledge of Japanese culture, and Japanese language proficiency increased. A good score on the test as well as a positive response given by the teacher shows the success of this activity.